Cultural Values Study of SITARO Society's Motto “Pakatiti Tuhema, Pakanandu Mangena, Boleng Balang Singkahindo” (As a Contribution for Culture Learning in Education) - Devilito Prasetyo Tatipang; Ceisy Nita Wuntu; Aprillya A. Suoth; Triesye A. Laloan (Universitas Batanghari Jambi, 2022)
The form of culture as a system of ideas is very abstract, cannot be touched or photographed and is contained in the minds of individuals who adhere to that culture. One form of culture in the SITARO community is a reflection of the SITARO community's motto, namely